Analisis Schedule Dan Fingerprint Pada Kinerja Karyawan Industri Tambang Di PT. Duta Tambang Rekayasa - Avid Styagung; Muhammad Ridwan Basalamah; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract Pressure will be realized if a number of individual respondents fail to meet the demands of their duties. In addition to the workload and work pressure of the agency, in this case the responsible person is the leader must also pay attention to the time Deadline problem because in providing an appropriate Deadline and does not seem to pressure employees in completing their work. has been given. Deadline time limit causes respondents to be required to complete a job immediately and if this is not achieved it will cause a conflict because the time specified for a job is passed and performance can be disrupted so that it will cause premature termination of the procedure. The demand for quality reports with a limited time is of course a special pressure for ASN employees in the inspectorate service in the Batu City Hall. Keywords: Work Pressure, Workload,Deadline